Perilaku Penjamah Makanan Dalam Penerapan Higiene Dan Sanitasi Pengolahan Makanan Di RSUD K.H. Hayyung Kabupaten Kepulauan Selayar - Inayah, Inayah; Sahani, Wahyuni; Ruhban, Andi (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Food handlers are the people responsible for food health. Food that is not managed properly and correctly by food handlers can cause negative impacts such as disease and poisoning, and can also cause allergies. Hygiene and health of food handlers and the environment are among the main requirements in food processing.The purpose of the study was to determine the behavior of food handlers in the application of food processing hygiene and sanitation at K.H. HAYYUNG Hospital, Selayar Islands Regency. This type of research is descriptive observational. With a sample size of 16 people in the nutrition installation.The results of this study are food handlers who have a high level of knowledge as many as 9 people (56%), as many as 9 people with (56%) who have a good attitude, as many as 10 people (62%) have good actions in implementing hygiene and sanitation of food processing and sanitary conditions of equipment and food processing places in good condition with a percentage of 86%.Suggestions in this study, to the manager of the Nutrition Installation to provide training to food handlers related to the application of good food processing hygiene and sanitation, it is also necessary to supervise food handlers and need to provide a closed cooking utensil storage area that meets the standards. As well as to further researchers to conduct research on the relationship between food handler behavior and conducting Total Plate Count (ALT) checks on tableware in the Nutrition Installation